As frentes de (des)articulação e resistência dos produtores agrícolas frente ao avanço da especulação imobiliária: um estudo de caso do bairro Mercês, Paço do Lumiar - MA - Lima, Ricardo Everton (2023)
The development of this research aims to analyze the forms of organization of the productive space of the farmers in front of the real estate speculation of the Mercês neighborhood, Paço do Lumiar - MA. The choice of location was due to the fact that it has an important history of family agricultural production, with outstanding supply to the ludovicense consumer market, and, over the last few years, it has been suffering from a territorial reduction, which directly impacts on social, cultural rites. and economic benefits of the neighborhood's residents. The understanding of this urban advance on the rural residues of the Island of Maranhão, goes through the analysis of the urban explosion that occurred in São Luís - MA from the 1960s, which led to its urban limits merged with the limits of the neighboring municipalities of São Luís. Paço do Lumiar and São José de Ribamar. The proximity between the mentioned municipalities made the real estate industry use the Luminense and Ribamarense territories for the implementation of several residential condominiums, largely to serve the population of the state capital, where three of them were located on Mercês, which generated several damages to the environment, emphasizing the silting and pollution of the Mercês River, the main water supplier for the population and agricultural production of that place. The scenario of urban growth within Mercês led farmers to seek new types of (re)organization, one of which was the formation of the Association of Family Farmers of the Mercês Community – ASCAFAM. For the displacement of this dissertation study, we opted for the use of Dialectical Historical Materialism, we understand that it will subsidize us in the complex contradictory analysis between rural and urban that involves the Mercês territory.